Great job for theater majors - Goldberg, Jan (McGraw-Hill, 2004)
Every college major gives students valuable skills and training, perfect for a wide range of careers. The Great Jobs for Theater Majors helps you assess your talents and skills for a job, target the perfect career, tailor your job search, present college majors as workplace assets, and much more!